Lenalidomide Synergistically Enhances the Effect of Dendritic Cell Vaccination in a Model of Murine Multiple Myeloma. Issue 8 (October 2015) - Nguyen-Pham, Thanh-Nhan; Jung, Sung-Hoon; Vo, Manh-Cuong; Thanh-Tran, Huong-Thi; Lee, Youn-Kyung; Lee, Hyun-Ju; Choi, Nu-Ri; Hoang, My-Dung; Kim, Hyeoung-Joon; Lee, Je-Jung
Abstract : We investigated the efficacy of lenalidomide (LEN) in combination with dendritic cell (DC) vaccination in the MOPC-315 murine myeloma model. After tumor growth, LEN was injected intraperitoneally for 4 consecutive days in combination with DC vaccination. The combination of LEN and vaccination efficiently inhibited tumor growth compared with the single agents alone. A cytotoxic assay revealed that the anticancer effects of DC vaccination plus LEN involved not only generation of antigen-specific cytotoxic T lymphocytes but also NK cells. Vaccinated mice had reduced numbers of suppressor cells, including both myeloid-derived suppressor cells and regulatory T cells, in the spleen. The proportions of CD4 + and CD8 + T cells increased in the spleen, and a Th1 cytokine (interferon- γ) rather than a Th2 cytokine (interleukin-10) was synthesized in response to tumor antigens. LEN enhanced the innate immune response by modulating NK cell numbers and function. In addition, LEN reduced the production levels of angiogenesis-inducing factors in tumor-bearing mice. Together, these results suggest that a combination of LEN and DC vaccination may synergistically enhance anticancer immunity in the murine myeloma model, by inhibiting immunosuppressor cells and stimulating effector cells, as well as effectively polarizing the Th1/Th2 balance in favor of a Th1-specific immune response.